Encyclopedia of sleep and circadian rhythms - Kushida, Clete Anthony, 1960- (Academic Press, 2023)
Encyclopedia of Sleep and Circadian Rhythms, Second Edition, Six Volume Set is the most comprehensive work on sleep and circadian rhythms. This completely revised new edition, comprised of contributions from 450 renowned authorities in the field, covers what is new and known in the field. In addition to thorough coverage of the basics (physiology, sleep disorders etc.), this new edition includes a thorough examination of circadian rhythms that manage the sleep-wake cycle. Although this area is highly intertwined with sleep, it is a scientific discipline in and of itself, and will broaden the appeal of this work to health care providers and scientists. Other sections of interest explore consumer wearable devices to track sleep and circadian rhythms, artificial intelligence algorithms to detect sleep and abnormal sleep-related conditions, and new technology to treat sleep and circadian rhythm disorders. This book will be an ideal and primary reference resource for students, trainees, technologists, basic/clinical scientists, physicians, advanced practice providers, psychologists, nurses, and other medical and research personnel who want to explore any topic within the sleep and circadian rhythm field.